Relatório de Estágio Profissional "O desafio e a paixão de ensinar" - Joana Alexandra Nunes Alves (2017)
This document is personal, was carried out within the scope of the second cycle of studies leading to the Master's Degree in Teaching Physical Education in Basic and Secondary Education, Faculty of Sport of the University of Porto. This document intends to explain to the reader the path taken by the trainee student during her internship year, her first year as a teacher, exposing the school context where the trainee was held, all the experiences experienced, the learning and objectives planned and achieved during the school year. This report represents the reflection throughout the year, guided by a faculty member and accompanied by a cooperating teacher, from the school where this same professional stage took place. The School is located in a Grouping of the district of Oporto, with two nuclei of three trainee students each, six in total. Structurally, the report covers five chapters: the first concerns the "Introduction", where the report attempts are present; In the second chapter, the "Personal Framework", where my academic life, previous and sporting experiences, culminating in the choice of this profession is evident, the initial expectations of the Professional Internship are also referenced in this chapter. The third chapter, referring to the "Institutional Framework", reports on the legal and institutional context of the Pedagogical Stage, as well as the characterization of the school and the classes with which I interacted during the school year. The fourth chapter refers to area 1 "Organization and Management of Teaching and Learning", which reveals planning, evaluation; To area 2 "Participation in School and Relationship with the Community", addresses the theme of the Class Director, School Sport (DE) and the activities developed; And Area 3 "Professional Development", where the learning activities carried out during the academic year in the college are present. In the fifth chapter is presented the research study on the subject of student satisfaction with the Curricular Unit: Sports Workshop. Finally, there are future conclusions and perspectives on the teaching profession.